2020
DOI: 10.3389/fcell.2020.00094
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of GSK3 Represses the Expression of Retinoic Acid Synthetic Enzyme ALDH1A2 via Wnt/β-Catenin Signaling in WiT49 Cells

Abstract: Organogenesis, including renal development, requires an appropriate retinoic acid concentration, which is established by differential expression of aldehyde dehydrogenase 1 family member A2 (ALDH1A2) and cytochrome P450 family 26 subfamily A/B/C member 1 (CYP26A1/B1/C1). In the fetal kidney, ALDH1A2 expresses in the developing stroma and renal vesicle and its derivatives but does not present in the ureteric bud. It remains unclear what may contribute to this expression pattern. Here we show that the glycogen s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 81 publications
(141 reference statements)
0
2
0
Order By: Relevance
“…The Wnt signaling pathway includes the canonical Wnt/β-catenin signaling pathway, the non-canonical Wnt/Ca 2+ signaling pathway, and the Wnt/planar cell polarity signaling pathway [ 14 ]. The classic Wnt/β-catenin signaling pathway is the most characterized Wnt pathway [ 15 ]; it is involved in various cellular functions, including cell proliferation, stem cell self-renewal, and organogenesis [ 15 17 ]. The Wnt/β-catenin signaling pathway is closely related to the occurrence and development of breast cancer, colon cancer, ovarian cancer, prostate cancer, and other malignant tumors.…”
Section: Introductionmentioning
confidence: 99%
“…The Wnt signaling pathway includes the canonical Wnt/β-catenin signaling pathway, the non-canonical Wnt/Ca 2+ signaling pathway, and the Wnt/planar cell polarity signaling pathway [ 14 ]. The classic Wnt/β-catenin signaling pathway is the most characterized Wnt pathway [ 15 ]; it is involved in various cellular functions, including cell proliferation, stem cell self-renewal, and organogenesis [ 15 17 ]. The Wnt/β-catenin signaling pathway is closely related to the occurrence and development of breast cancer, colon cancer, ovarian cancer, prostate cancer, and other malignant tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (2019) Overexpression miR‐144‐5p could inhibit proliferation and induce apoptosis in human umbilical vein endothelial cells (HUVECs) via targeting SMAD1. Li et al (2020) A previous study found that miR‐193b‐3p plays a pivotal role in inflammatory (Arner et al, 2012; Chen et al, 2020; Lai et al, 2020), and regulation of miR‐193b‐3p expression may become a potential therapeutic strategy to ameliorate AS. Therefore, the present study aimed to investigate the role of miR‐193b‐3p in AS.…”
Section: Introductionmentioning
confidence: 99%